EMPOWERMENT OF THE MELAPI VILLAGE COMMUNITY THROUGH TRAINING ON BIO-VETSIN MAKING FROM SENGKUBAK LEAVES (PYCNARRHENA CAULIFLORA) - Nurdiansyah; Diah Mustika Lukitasari; Hamidun; Hetty Sri Mulyati; Muhammad Syafi'ie; Dody Radiasah; Syarif Muhammad Ilham; Ridho Dwi Syahrial (RADJA PUBLIKA, 2025)
The Community Service Program (PKM) focuses on empowering the people of Melapi Village through training in making bio-vetsin from Sengkubak leaves (Pycnarrhena cauliflora), which is a natural alternative to MSG. The goal is to optimize local potential by improving knowledge and hygiene processing skills as well as mastery of appropriate technology. The method used is Participatory Rural Appraisal (PRA) with an interactive lecture approach, demonstration, and hands-on practice (learning by doing). The results showed an increase in participants' knowledge by 45% (pre-test and post-test scores) and 85% of participants were skilled in operating processing equipment. This program has succeeded in producing ready-to-sell bio-vetsin products, opening up sustainable economic opportunities, and preserving the local wisdom of Melapi Village.